Experiences with cancer survey in China. Issue 17 (8th May 2019) - Yao, Nengliang; Zhang, Nan; Wang, Jialin; Anderson, Roger T.; Liu, Xinting; Lyu, Jingru; Du, Xiwen; Sun, Xiaojie
Abstract : Background: China accounts for approximately 27% of global cancer deaths. However, to the authors' knowledge, the lasting effects of cancer and cancer treatments on patients have not been investigated in China. The authors developed a questionnaire, the China Survey of Experiences with Cancer, for Chinese cancer survivors. This article introduces the study design and domains covered in the questionnaire. Methods: The Cancer Survivorship Supplement of the Medical Expenditure Panel Survey (MEPS) was used as a reference to develop the questionnaire. The final in‐person surveys were conducted in 2015 and 2016. Samples were chosen through multistage sampling. The authors described the characteristics of the study participants and their cancer experiences. Results: At the time of last follow‐up, a total of 1166 patients had completed at least 1 component of the survey. Approximately 59% of the cancer survivors were aged ≥60 years. Greater than one‐half of the participants had an elementary education level or less (51%) and a yearly family income of <$3174. Chinese cancer survivors were more likely to retire earlier than planned compared with American cancer survivors (37% vs 9%). The majority of Chinese cancer survivors (84%) reported that their work abilities were hindered by their cancer or cancer treatments. Approximately one‐half of patients in China had to incur debt because of cancer, whereas <10% of patients in the United States reported having incurred debt. Conclusions: The survey provides information regarding the burden of cancer in China that to the authors' knowledge currently is unavailable from other sources, including medical care use, financial impacts, employment patterns, and life experience after a cancer diagnosis for survivors and their families. Abstract : China accounts for approximately 27% of global cancer deaths. In the current study, the authors have developed a questionnaire, the China Survey of Experiences with Cancer, for Chinese cancer survivors. This questionnaire provides information regarding the burden of cancer in China that currently is unavailable from other sources, including medical care use, financial impacts, employment patterns, and life experience after a cancer diagnosis for survivors and their families.